Reactions of some cucumber (Cucumis sativus L.) lines and hybrids to zucchini yellow mosaic virus (ZYMV) and selection of tolerant breeding lines - Salamon, P.; Balogh, P. (International Journal of Horticultural Science, 1999)
In the past years zucchini yellow mosaic virus (ZYMV) has been appeared as a new pathogen of cucurbitaceous plants in Hungary. It caused severe disease outbreaks on the fields of pickling cucumber hybrids which are highly tolerant to cucumber mosaic virus (CMV). Preliminary inoculation tests have showed that all of the important pickling cucumber hybrids produced in Hungary were susceptible to ZYMV-P. However, a selection of Chinese Long and the breeding line I- KS 10C proved to be highly tolerant. The Fl plants of the crosses between the tolerant lines and the susceptible genotype H I were susceptible to ZYMV-P. F2 populations segregated for susceptible and tolerant individuals at a ratio of 3:1. The results strongly suggest that the resistance to ZYMV in our sources is controlled by a single recessive gene. Inoculations of the ZYMV and CMV susceptible cultivar Budai csemege and the CMV tolerant hybrid Perez Fl with the complex of ZYMV+CMV resulted extremely severe symptoms (strong mosaic and necrotic spotting of the leaves) on both cultivars. On the Chinese Long line, which is tolerant to ZYMV and CMV, respectively, the complex of the two viruses caused mild symptoms. The results show a synergistic pathological effect of ZYMV and CMV on differrent cucumber genotypes. More detailed studies on the interactions among the plant genotypes, viruses and virus strains are needed to develop cucumber hybrids that are highly resistant to the ZYMV+CMV complex.